Challenges and opportunities for siRNA-based cancer treatment. (28th February 2017) - Wang, Tao; Shigdar, Sarah; Shamaileh, Hadi Al; Gantier, Michael P.; Yin, Wang; Xiang, Dongxi; Wang, Lan; Zhou, Shu-Feng; Hou, Yingchun; Wang, Peng; Zhang, Weihong; Pu, Chunwen; et al.
Highlights: Distinct rules for chemical modification of siRNA and antisense oligonucleotide. Optimised research model leads to predictable bio-distribution pattern of siRNAs. Characterisation of endosomal escape aids future siRNA-based cancer treatment. Gene target selection – cancer stem cell critical genes and multiple gene targeting. Appropriate research controls and 5′RACE assay ensure minimum off-target effect. Abstract: As one of the life-threatening diseases involving multi-step genetic and epigenetic disorders, cancer has long been a dynamic research area for siRNA-based therapy as half of the current siRNA-based clinical trials are involved in oncology. However, despite consistent enthusiasm in the academic world, siRNA-based cancer treatment still faces obstacles and difficulties in clinical development. In this article, we discuss key challenges facing siRNA-based cancer treatment revealed from recent clinical and preclinical studies, including chemical modification, tumour penetration, endosomal escape, target selection and off-target effects. In addition, opportunities and avenues for translating siRNA technology from bench to oncologic clinics are explored.